2021
DOI: 10.21763/tjfmpc.895883
|View full text |Cite
|
Sign up to set email alerts
|

15-49 Yaş Kadınlarda Kendiliğinden ve İsteyerek Düşükler ve Belirleyicileri

Abstract: Aim: Abortions, which are among the causes of maternal mortality in the world, continue to be important not only for women's health, but also because they have devastating physiological, psychological, and economic effects on the family and society. The present study aimed to determine the prevalence of total, induced, and spontaneous abortion in women aged 15-49 in a Family Health Center (FHC) region, and the factors affecting the abortion prevalence. Methods: This cross-sectional study was conducted with 311… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
0
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
2
0
0
2
Order By: Relevance
“…According to this study, women who used drugs or alcohol were more likely to have an induced abortion than those who did not. This result is consistent with a study conducted in Turkey [ 73 ]. This suggests that the association between drug and alcohol use and induced abortion is not specific to a particular region or country.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…According to this study, women who used drugs or alcohol were more likely to have an induced abortion than those who did not. This result is consistent with a study conducted in Turkey [ 73 ]. This suggests that the association between drug and alcohol use and induced abortion is not specific to a particular region or country.…”
Section: Discussionsupporting
confidence: 94%
“…Our study found a strong association between unintended at the time of pregnancy and induced abortion, with women who had unintended at the time of pregnancy being nearly ten times more likely to undergo induced abortion compared to those with intended at the time of pregnancy. This finding is consistent with previous studies from around the world, including Turkey, Iran, and India [ 6 , 73 , 80 , 81 ], which have also demonstrated a significant relationship between unintended at the time of pregnancy and induced abortion. These results highlight the importance of addressing unintended at the time of pregnancy through effective family planning programs and education to reduce the incidence of induced abortion and improve women’s reproductive health.…”
Section: Discussionsupporting
confidence: 93%
“…8 Çetinkaya ve Mercan çalışmalarında her 5 kadından birinin istenmeyen gebelik yaşadığını, 10 kadından birinin isteyerek düşük yaptığını ve kadınların %54'ünün Türkiye'de isteyerek düşük/kürtajın yasal olduğunu bilmediklerini belirlemiştir. 12 Bu çalışmada da kadınların çoğu daha önce düşük/kürtajın yapılabileceği yasal süreyi bilmediklerini veya bu süreçte öğrendiklerini belirtmiştir. Ayrıca kadınlar düşük/kürtaj sonrası önemli sağlık problemleri yaşamışlar ve bu süreçte sağlık hizmeti talep etmemişlerdir.…”
Section: Discussionunclassified
“…8 Gelir düzeyi düşük kadınlar özellikle risk altındadırlar. 12 Bu çalışmada görüldüğü gibi düşük/kürtaj ihtiyacı ortaya çıktığında kadınlar güvenli ve ücretsiz olan kamu hizmetlerine kolayca erişemedikleri zaman, mahremiyetlerinin korunacağı düşüncesiyle özel hekimleri ve klinikleri tercih etmektedirler. Özellikle genç ve bekâr kadınlar, damgalanma korkusuyla ücretsiz ve daha güvenli olan kamu hizmetlerini tercih etmek yerine maliyeti daha yüksek olan ve kimi zaman güvenli olmayan koşullarda verilen "özel" hizmetleri tercih edebilmekte veya kendi yöntemleriyle düşük yapabilmektedirler.…”
Section: Discussionunclassified